Dampak dan Upaya Pencegahan Stigmatisasi Masyarakat terhadap Pasien Covid-19 di Badung-Bali - Hesteria Friska Armynia Subratha; Indra Peratiwi (LPPM STIKes ICsada Bojonegoro, 2022)
The pandemic is one of the most serious public health problems globally. This is like what happened in early 2020 when the COVID-19 outbreak first occurred in Wuhan. The threat of this pandemic is getting bigger when various cases show that transmission can occur between humans (human to human transmission). However, in this case, many Covid-19 sufferers are stigmatized. This study aims to determine the impact and efforts to prevent community stigmatization of Covid-19 patients in 2021. This study uses a qualitative descriptive study with observation methods and in-depth interviews with health workers with 8 positive cases of COVID-19 and 2 respondents who were not confirmed positive. . This research was conducted from March 1 – March 6, 2021. The results of this study indicate that the emergence of stigmatization during the COVID-19 pandemic was based on the lack of public knowledge, supported by unverified information or uncontrolled fake news which caused concern and fear. people who are excessive so that they have incorrect perceptions and carry out discriminatory treatment. Effective prevention that can be done to minimize stigma is the provision of education or education in the form of health campaigns and promotions to the community as well as screening of hoax news so that the public gets information from credible official sources.